2021
DOI: 10.46542/pe.2021.212.281286
|View full text |Cite
|
Sign up to set email alerts
|

Proximate analysis on animal feed granules composed of raw material from fish innards wastes

Abstract: Introduction: Fish innards contain 14.01% protein, 20% lipid, 4.75% ash, and 60.62% water. Fish innards are formulated into granules for practicality in their application as animal feed. Aim: This research on the proximate analysis of animal feed granules composed of raw material from fish innards wastes used a descriptive quantitative method. Results: The result indicated that the water content measured using the thermogravimetric method was 6.62%, the ash content observed using the dry ashing method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The quantity of water accessible in dry sample of a solid biomass is moisture content and its higher quantity in biofuel reduces quality (Sukarni et al 2019;Maksimuk et al 2021) therefor for effective quality, its value should be less than 10 (Fadhil et al 2017). The moisture content of all feedstocks in present study were within range compared to other reported studies (Gusain et al 2017;Maktoof et al 2020;Setyani et al 2021). Volatile matter is majorly comprises of hydrogen gas, hydrocarbons, carbon dioxide, and some tar (Zhuang et al 2021).…”
Section: Proximate Analysis (Characterization) Of Feedstocksupporting
confidence: 79%
“…The quantity of water accessible in dry sample of a solid biomass is moisture content and its higher quantity in biofuel reduces quality (Sukarni et al 2019;Maksimuk et al 2021) therefor for effective quality, its value should be less than 10 (Fadhil et al 2017). The moisture content of all feedstocks in present study were within range compared to other reported studies (Gusain et al 2017;Maktoof et al 2020;Setyani et al 2021). Volatile matter is majorly comprises of hydrogen gas, hydrocarbons, carbon dioxide, and some tar (Zhuang et al 2021).…”
Section: Proximate Analysis (Characterization) Of Feedstocksupporting
confidence: 79%
“…The content of water-soluble protein was determined according to the Biuret method described in Setyani's work [30]. The molecular mass distribution of water-soluble protein was determined using Tricine-SDS-PAGE.…”
Section: Protein Characterizationmentioning
confidence: 99%